Pengaruh Urban Sprawl terhadap Kondisi Fisik Kota: Studi Kasus Kecamatan Bojongloa Kidul - Wanda Yolanda; Sri Hidayati Djoeffan (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Urban sprawl is an unplanned urban development due to the tendency of residents to live in suburban areas. Bojongloa Kidul District is a sub-district located in a suburban area bordering Bandung Regency. Bojongloa Kidul District in 2005 was the District with the lowest urban sprawl typology, and in 2018 it became the highest urban sprawl typology. The purpose of this study was to determine the effect of urban sprawl on the physical condition of the city in Bojongloa Kidul District. The method is a mixed method with quantitative and qualitative analysis techniques. The stages of the analysis method in this study are the analysis of the identification of the sprawl area, the analysis of the characteristics of the sprawl using population density analysis, analysis of building density, analysis of the distance to the center of the CBD, and analysis of development within the reach of the road network, analysis of the ANOVA statistical method. Based on the results of the study, it shows that the urban sprawl indicated urban sprawl in 2011 and 2021 are Cibaduyut, Cibaduyut Kidul, Cibaduyut Wetan, and Mekarwangi villages. Abstrak. Urban sprawl merupakan perkembangan kota yang tidak terencana karena kecenderungan penduduk untuk bermukim di area pinggiran kota. Kecamatan Bojongloa Kidul yang berada di area pinggiran kota berbatasan dengan Kabupaten Bandung. Kecamatan Bojongloa Kidul pada tahun 2005 merupakan Kecamatan dengan tipologi urban sprawl paling rendah sedagkan tahun 2018 menjadi tipologi urban sprawl paling tinggi. Tujuan dalam penelitian ini adalah untuk mengetahui pengaruh urban sprawl terhadap kondisi fisik kota di Kecamatan Bojongloa Kidul. Metode dalam penelitian ini adalah mixed method dengan teknik analisis kuantitatif dan kualitatif. Tahapan analisis dalam penelitian ini adalah analisis identifikasi kawasan sprawl, analisis karakteristik sprawl menggunakan analisis kepadatan penduduk, analisis kepadatan bangunan, analisis jarak ke pusat CBD, dan analisis pembangunan dalam jangkauan jaringan jalan, analisis metode statistik ANOVA. Berdasarkan hasil penelitian menunjukkan bahwa Kelurahan yang terindikasi urban sprawl pada tahun 2011 dan 2021 adalah Kelurahan Cibaduyut, Cibaduyut Kidul, Cibaduyut Wetan, dan Mekarwangi.